(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2020)
This study aims to evaluate in more detail the Good Practices Guide and Guidelines for Electronic Commerce Platforms published by the Nacional Anti-Piracy Council and Intellectual Property Offenses, published on April 23th, 2020, which has with the objective of implementing repressive and preventive measures in order to fights against piracy and counterfeiting sales, that violate intellectual property . The objective was to evaluate all points considered in the Guide, seeking to present a systematic form to users.